Egzegeza literalna Starego Testamentu jako źródło herezji. Stanowisko Filastriusza z Brescii - Szram, Mariusz (Vox Patrum, 2018)
In the last part of the treatise Diversarum hereseon liber (from chapter 128 to 156), Filastrius of Brescia presents heresies based on the erroneous exegesis of the various biblical texts of the Old Testament. The author of the article discusses several examples of the exegesis considered by Filastrius to be heretical, and wonders whether they indeed had signs of heresy and whether they could pose a significant threat to ecclesiastical orthodoxy. In the light of the examined texts, the Bishop of Brescia appears as a follower of the allegorical exegesis. As for the whole of the Alexandrian tradition from Origen, the overriding criterion of orthodox interpretation of the Scriptures was a spiritual advantage (utilitas spiritalis, scientia caelestis, scientia salutaris). If the proposed interpretation of the biblical text not carried out for such spiritual benefit, it was designated by the Bishop of Brescia as heretical, even if it did not materially harm the doctrinal truths contained in the Rule of the Church’s faith.